2022
DOI: 10.7573/dic.2022-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Advanced non-small-cell lung cancer: how to manage non-oncogene disease

Abstract: The therapeutic approach to patients affected by advanced non-small-cell lung cancer (NSCLC) is facing rapid and continuous evolution. In recent years, the emergence of new treatment strategies, such as immunotherapy and tyrosine kinase inhibitors, has revolutionized the treatment algorithm and the prognosis of patients with NSCLC. In the nononcogene-addicted disease, immune-checkpoint inhibitors, either as single agents or combined with chemotherapy, outperformed standard chemotherapy in both untreated and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Our study confirmed that baseline ECOG PS ≥ 2 was associated with early mortality. Treating patients with ECOG PS ≥ 2 remains an open debate as prospective randomized trials usually exclude these patients, and thus, data mostly derive from retrospective analyses [ 1 ]. Still, some phase 2 prospective trials suggested that the toxicity profile of immunotherapy for frail patients is acceptable even if the efficacy may be reduced [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study confirmed that baseline ECOG PS ≥ 2 was associated with early mortality. Treating patients with ECOG PS ≥ 2 remains an open debate as prospective randomized trials usually exclude these patients, and thus, data mostly derive from retrospective analyses [ 1 ]. Still, some phase 2 prospective trials suggested that the toxicity profile of immunotherapy for frail patients is acceptable even if the efficacy may be reduced [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, ICI constitute the first-line backbone for non-oncogene addicted advanced NSCLC. The addition of chemotherapy improved survival outcomes compared with standard chemotherapy, and to date, no head-to-head comparisons have been performed with ICI as single agents, which is of remarkable interest, especially for NSCLCs with high PD-L1 expression (≥50% tumor proportion score) [ 1 , 25 ]. In this setting, the combination strategy may prevent early progression and improve the response rate, and the decision may be driven by clinical conditions or high tumor burden [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 65 However, tumor PD-L1 expression is not completely reliable, as improved survival outcomes have also been assessed in negative or low PD-L1 expression, even if the 50% of tumor proportion score represents the best threshold for upfront single-agent PD-(L)1 inhibitor efficacy as demonstrated by several prospective trials. 66 Tumor mutational burden (TMB) is defined as the total number of somatic, non-synonymous mutations in the tumor genome. It is garnering a lot of attention, and several studies have reported the evaluation of TMB in blood (bTMB) as this may be estimated from cfDNA NGS.…”
Section: Applications Of Liquid Biopsymentioning
confidence: 99%
“…The elucidating of immune-escape cancer mechanisms led to the development of immunotherapeutic agents such as monoclonal antibodies directed against the programmed death 1 (PD-1) receptor or its ligand (PD-L1) or the CTLA4 receptor. 1 Therefore, immunotherapy progressively became the backbone of upfront strategy as single agents or in combination with other agents (immunotherapy, chemotherapy) for advanced NSCLC without oncogenic driver alterations. 1 In this context, the rapidly expanding armamentarium and lack of predictive biomarkers other than PD-L1 intratumoural expression poses a challenge to physicians in daily practice and fosters the debate about translational studies.…”
Section: Editorialmentioning
confidence: 99%